Mechatronic Futures Challenges and Solutions for Mechatronic Systems and their Designers - Hehenberger, Peter; Bradley, David; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Offering a comprehensive overview of the challenges, risks and options facing the future of mechatronics, this book provides insights into how these issues are currently assessed and managed. Building on the previously published book 'Mechatronics in Action,' it identifies and discusses the key issues likely to impact on future mechatronic systems. It supports mechatronics practitioners in identifying key areas in design, modeling and technology and places these in the wider context of concepts such as cyber-physical systems and the Internet of Things. For educators it considers the potential effects of developments in these areas on mechatronic course design, and ways of integrating these. Written by experts in the field, it explores topics including systems integration, design, modeling, privacy, ethics and future application domains. Highlighting novel innovation directions, it is intended for academics, engineers and students working in the field of mechatronics, particularly thosedeveloping new concepts, methods and ideas.
System Integration -- Design -- Demographics -- Human -- Machine Interaction -- Ethics -- Manufacturing Technology -- Sustainability -- Education -- Future Application Domains.
Keywords: Control engineering; Robotics; Automation; Engineering design; Mathematics -- Data processing; Control, Robotics, Automation; Engineering Design; Computational Science and Engineering